The Role of Pulmonary Rehabilitation and Physical Activity in the Prevention, Treatment and Management of Respiratory Diseases - A Comprehensive Review - Krzykawski, Karol; Maciejczyk, Tomasz; Mól, Piotr; Sadowski, Jakub; Zabawa, Bartłomiej; Dołęga, Julia; Papież, Łukasz Stanisław; Hudzińska, Patrycja; Sieńko, Antoni; Łabuś, Małgorzata (Quality in Sport, 2024)
Introduction: Chronic respiratory diseases, including chronic obstructive pulmonary disease, asthma, obstructive sleep apnea, and other restrictive lung disorders, represent a growing global health challenge. These conditions not only affect an increasing portion of the population but also impose significant burdens on public health systems. Lifestyle factors such as smoking, air pollution, and coexisting conditions critically influence the progression and severity of these diseases. The profound impact on mortality, quality of life, and associated complications underscores the need for interventions that extend beyond symptom control. Comprehensive patient education, psychological support, and integrated healthcare strategies are essential for effectively addressing these challenges. Materials and Methods: A thorough review of literature was conducted using databases like PubMed, NCBI, and Google Scholar. Search terms included “pulmonary rehabilitation,” “physical activity,” “respiratory system diseases,” and “respiratory symptoms”. State of knowledge: Pulmonary rehabilitation is a therapy designed for individuals with chronic respiratory diseases. A core component consists of supervised physical training, complemented by nutritional counseling, psychological support, and disease management education. Pulmonary rehabilitation has demonstrated effectiveness in improving lung function, exercise capacity, and alleviating dyspnea. Additionally, the integration of psychological aspects further benefits patients by reducing anxiety and enhancing symptom control. Furthermore, regular physical activity has been shown to reduce the risk of pneumonia and lung cancer. Conclusions: Pulmonary rehabilitation improves physical activity, exercise tolerance, and quality of life, while reducing symptoms. It also lowers the risk of severe lung diseases. As such, it should be a key component of both treatment and prevention, offering effective, holistic approach to patient care.